2017
DOI: 10.1142/s0219477517500134
|View full text |Cite
|
Sign up to set email alerts
|

Noise Modeling in MOX Gas Sensors

Abstract: In this paper, we propose a new model of adsorption–desorption (AD) noise in chemoresistive gas sensors by taking into account the polycrystalline structure of the sensing layer and the effect of the adsorbed molecule’s density fluctuation on the grain boundary barrier height. Using Wolkenstein’s isotherm, in the case of dissociative and non-dissociative chemisorption, combined with the electroneutrality, we derive an exact expression for power density spectrum (PDS) of the AD noise generated around one grain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 17 publications
4
28
1
Order By: Relevance
“…However below this frequency, the overall spectrum of the gas sensor noise is a combination of multi Lorentzians. This result was shown in our previous paper [25]. Moreover, in the model presented in our previous paper [25], we have shown that the number of lorentzians is independent of the nature of the detected gas.…”
Section: A Noise Responses Under Different Gasessupporting
confidence: 85%
See 4 more Smart Citations
“…However below this frequency, the overall spectrum of the gas sensor noise is a combination of multi Lorentzians. This result was shown in our previous paper [25]. Moreover, in the model presented in our previous paper [25], we have shown that the number of lorentzians is independent of the nature of the detected gas.…”
Section: A Noise Responses Under Different Gasessupporting
confidence: 85%
“…In our previous work [25], we have developed a model of noise in metallic-oxide gas micro sensors. We have shown that the adsorption-desorption (A-D) noise generated in the overall sensing layer is a combination of multi-Lorentzian components.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 3 more Smart Citations